Development of non-viral vehicles for targeted gene transfer into microglia via the integrin receptor CD11b - Smolny, Markus; Rogers, Mary-Louise; Shafton, Anthony; Rush, Robert A.; Stebbing, Martin J. (Frontiers in Molecular Neuroscience, 2014)
Microglial activation is a central event in neurodegeneration. Novel technologies are sought for that specifically manipulate microglial function in order to delineate their role in onset and progression of neuropathologies. We investigated for the first time whether non-viral gene delivery based on polyethyleneglycol (PEG)-polyethyleneimine (PEI) conjugated to the monoclonal anti-CD11b antibody OX42 (‘OX42-immunogene’) could be used to specifically target microglia. We identified the microglial integrin receptor CD11b as a potential target for receptor-mediated gene transfer based on its cellular specificity in mixed glia culture and in vivo and found that the OX42 antibody is rapidly internalized and trafficked to acidic organelles in absence of activation of the respiratory burst. We then showed that the OX42-immunogene although internalised was degraded intracellularly and did not cause substantial gene expression in microglia. Investigation of specific barriers to microglial gene transfer revealed that aggregated OX42-immunogene polyplexes stimulated the respiratory burst that likely involved Fcγ-receptors. Transfections in the presence of the endosomolytic agent chloroquine improved transfection efficiency indicating that endosomal escape may be limited. This study identifies CD11b as an entry point for antibody-mediated gene transfer into microglia and takes important steps towards the further development of OX42-immunogenes.